Islamic Work Ethics and Organizational Commitment: The Role of Cultural Factors as a Moderator for Early Childhood Education Teachers - Nadhirotul Laily; Retno Dwiyanti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Islamic work ethics is a set of value systems and beliefs in educators that are sourced from Islamic teachings and underlie the attitudes and behavior of Early Childhood Education (PAUD) teachers in increasing organizational commitment strengthened by cultural factors. The objectives of this study are (1) to determine the influence of Islamic work ethics on organizational commitment (2) to test cultural factors as a moderator of the relationship between Islamic work ethics and organizational commitment in PAUD teachers. The subjects in this study were PAUD Aisyiyah Bustanul Athfal (ABA) teachers in Gresik Regency, East Java and PAUD ABA teachers in Purwokerto Regency, Central Java using random sampling obtained 172 participants. Data collection instruments used the Islamic Work Ethic Questionnaire, Organizational Commitment Questionnaire, and cultural demographic data. This type of research is quantitative, and in data analysis using PLS-SEM analysis. The results of the study showed that there was a significant influence of Islamic work ethics on organizational commitment with p <0.01, while cultural factors did not moderate the relationship between Islamic work ethics and organizational commitment with p = 0.157. These findings indicate that internalized Islamic values within educators are consistently able to predict organizational commitment, regardless of differences in cultural background.Etika kerja Islam menjadi seperangkat sistem nilai dan keyakinan pada pendidik yang bersumber dari ajaran agama Islam serta mendasari sikap dan perilaku guru Pendidikan Anak Usia Dini (PAUD) dalam meningkatkan komitmen organisasi yang dikuatkan dengan faktor budaya. Tujuan dari penelitian ini adalah (1) untuk mengetahui pengaruh etika kerja Islam terhadap komitmen organisasi (2) menguji faktor budaya sebagai moderasi antara etika kerja Islam dengan komitmen organisasi pada guru PAUD. Subjek dalam penelitian ini adalah guru PAUD Aisyiyah Bustanul Athfal (ABA) di Kab. Gresik Jawa Timur dan guru PAUD ABA di Kab. Purwokerto Jawa Tengah menggunakan random sampling didapatkan sebanyak 172 parisipan. Instrumen pengumpulan data menggunakan Islamic Work Ethic Questionnaire, Organizational Commitment Questionnaire, dan data demografi budaya. Jenis penelitian ini adalah kuantitatif, dan dalam analisis data menggunakan analisis PLS-SEM. Hasil penelitian menunjukkan terdapat pengaruh signifikan etika kerja Islam terhadap komitmen organisasi dengan p < 0.01, sedangkan faktor budaya tidak memoderasi hubungan etika kerja Islam terhadap komitmen organisasi dengan p = 0.157. Temuan ini mengindikasikan bahwa nilai-nilai islam terinternalisasi dalam diri pendidik secara konsisten mampu memprediksi komitmen organisasi, terlepas dari perbedaan latar belakang budaya.